2020
DOI: 10.1097/md.0000000000021016
|View full text |Cite
|
Sign up to set email alerts
|

The association of obesity with health insurance coverage and demographic characteristics: a statewide cross-sectional study

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
23
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 34 publications
5
23
1
Order By: Relevance
“…While we followed similar definitions and methods, our sample was not restricted to Medicare FFS patients, and post-IPTW, approximately one-third of our cohorts had a third-party payer. It is well understood that patients vary by insurance status in terms of sociodemographic and clinical characteristics such as race, age, income status, presence of comorbid conditions, receipt of treatment, and health outcomes [ 36 , 37 , 38 ]. For example, one study showed that patients with Medicare insurance constitute a greater percentage of influenza-related inpatient stays as compared to influenza-related ED visits [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While we followed similar definitions and methods, our sample was not restricted to Medicare FFS patients, and post-IPTW, approximately one-third of our cohorts had a third-party payer. It is well understood that patients vary by insurance status in terms of sociodemographic and clinical characteristics such as race, age, income status, presence of comorbid conditions, receipt of treatment, and health outcomes [ 36 , 37 , 38 ]. For example, one study showed that patients with Medicare insurance constitute a greater percentage of influenza-related inpatient stays as compared to influenza-related ED visits [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, one study showed that patients with Medicare insurance constitute a greater percentage of influenza-related inpatient stays as compared to influenza-related ED visits [ 36 ]. Studies have found that the prevalence of obesity, diabetes, and other chronic conditions is higher in Medicare beneficiaries as compared to commercially insured adults [ 37 ]. Therefore, it is plausible that the inherent variations in sample characteristics between the two studies could be associated with differences in study outcomes.…”
Section: Discussionmentioning
confidence: 99%
“… 4 The rate of obesity has almost tripled globally in the last decades, with an estimated 1.9 billion adults overweight. 5 Although obesity has become a pandemic and a major burden in one of the high-income countries in Kingdom of Saudi Arabia. 6 Body Mass Index (BMI) is widely used for diagnosing obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Findings with respect to internet access [ 28 ] parallel those of the underserved in the United States. Moreover, not to imply that being on Medicaid causes poor health outcomes, there is literature suggesting that Medicaid beneficiaries have poorer health outcomes that can lead to long-term cardiovascular complications compared to privately insured individuals [ 29 ].…”
Section: Introductionmentioning
confidence: 99%